RANCANG BANGUN VISUALISASI LAGU MARS UNIVERSITAS STIKUBANK SEMARANG (Information Technology and Telematics, 2016)
ABSTRACTIn today's information age,  information delivery done in various ways have advantages and disadvantages of each  -  each. One way of delivering information at this time is through the medium of video clips, the submission of information by this method  is  considered  quite  effective,  especially  when  used  to represent  the information  to  be  conveyed  by  the  musicians.  Advances  in  technology  also  have  a  major impact on the progress and development of the multimedia industry, as well as the development of the music industry today are also growing more rapidly. In the development  of  the  music  industry  today  not  only  displays  the  audio,  but  also  requires  a  visual  animations  that  can  improve  product  quality  and  increase  the attractiveness of the community to enjoy music. Video clip is an animated visual that not  only  as  a  complement  to  the  music  but  also  as  a  media  campaign  that  can increase the attractiveness of the community.The  objective  of  this  research  is  to  design  and  create  a  visualization  song Mars University Stikubank Semarang as a medium to deliver information that can be enjoyed  by  the  community  so  it  can  manarik  concern  about  the  existence  of  the University Stikubank Semarang and students more familiar neighbor identity of the University  Stikubank  Semarang  through  the  delivery  of  video  animation  clips  song Mars University Stikubank Semarang.This study uses a methodology Multimedia Development. which consists of six  stages,  namely  the  concept,  design,  collecting  materials,  assembly,  testing  and distribution.Results  of this  research  is  a  Visualization  Design  of  Mars  song  Stikubank University Semarang is a video clip that is packaged in an animated and interesting CD Video Clips Stikubank Semarang Mars song that can be used at any time ready to recognize the tracks Stikubank University of Semarang.Keywords: Video clips, animation, design of